Innovation of service design based on TRIZ : a case study - Yong, Chin Bing (2017)
It is increasing hard to thrive in today’s business world. Good service design is the key to carrying out competitiveness so as to compete with the other competitors. Not only a good service could increase revenue, it can also significantly reduce time costs and increase customer satisfaction. This paper uses the Kobayashi Optical as a case study and applies the tools of Theory of Inventive Problem Solving (TRIZ) to analyze the context of the case company and generate innovation solutions. At the end of the analysis, a few solutions are generated. This study first gathers information by surveying over 80 people to understand the pain point of the customers. The information is then being further analyzed in the problem definition stage. A total of 12 discomforts and 2 problems are discovered. The two main problems found in the eyewear industry are 1) High inventory costs due to overstocking of the lens of frames 2) Different needs of each retail location causes difficulty in purchasing the correct amount of lens and frames. The 12 discomforts are: 1)Hard to find Suitable pair of glasses, 2)Too many choices, 3)Too little choices 4)Not all the designs are available, 5)Expensive, 6)Waiting time is too long, 7)Inaccurate eye test, 8)Inconvenience in collection of glasses, 9)Price varies from shop to shop, 10) Staff is unfriendly and 11) Staff lacks knowledge. Problem formulator is used to form problem statements, which could be used to resolve the discomforts and problems. In the problem resolution, contradiction matrix is employed to discover six TRIZ innovative principles to resolve the problem, which are 10-prior action, 11- beforehand cushioning, 28-mechanics substitution, 32-color changes, 34-discarding and recovering, 35-parameter changes. Based on these principles, a new service named “smart optical retail service” is designed and proposed. Smart optical retail service includes four main modules, namely 1) E-commerce platform with virtual try out app; 2) Chat bots; 3)Mobile eye testing machine; 4) Pre-ordering.